The Modern American Family in The Easter Parade - Gao, Anqi (Journal of Literature and Arts Research, 2025)
In the work The Easter Parade, Richard Yates takes the perspective of two sisters, Sarah and Emily, to expose the dilemmas faced by the modern American family in the mid-twentieth century. He focuses on the changes in the shape of the family and the mental state of people in family relationships, especially the fate of women in the family. This paper combines the family systems theory to sort out and interpret the family patterns in The Easter Parade, and analyses the modern American family in Yates' works.